The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/0092055x12465295
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Focus Group Interviewing

Abstract: Focus group interviewing is widely used by academic and applied researchers. Given the popularity and strengths of this method, it is surprising how rarely focus group interviewing is taught in the undergraduate classroom and how few resources exist to support instructors who wish to train students to use this technique. This article fills the gap in the teaching and learning literature in sociology by addressing focus group research. I describe how to integrate a complete research project with student-led foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…Like similar studies [28,29], we find that engaging undergraduates in a semester-long research project benefits undergraduate students. Students benefit from a hands-on research experience that deepens their understanding of both survey methods and social issues that they can use in the workplace or in graduate school.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Like similar studies [28,29], we find that engaging undergraduates in a semester-long research project benefits undergraduate students. Students benefit from a hands-on research experience that deepens their understanding of both survey methods and social issues that they can use in the workplace or in graduate school.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, with the safety training and precautions taken, faculty felt that surveying residents in the field posed little risk to students. For communities or neighborhoods with relatively high crime rates, a different methodology may be necessary for students to participate in community-based research, such as leading focus groups [28] or conducting in-depth interviews [26,30,31]. These methodologies allow students to gain knowledge about community issues, but in a more controlled setting such as a place on campus.…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of these types of experiences on the students themselves has been extensively studied. Much of the research in this area has focused on STEM fields (Zhan, ), but benefits have also been found in sociology (George, ), education (Burrows, Thomas, Woods, Suess, & Dole, ), and liberal arts (Richman & Alexander, ).…”
Section: Repurposing Datamentioning
confidence: 99%
“…Focus groups are an established mechanism for data collection across qualitative, mixed method, and quantitative methodologies (Pearson & Vossler, 2016). Although employed differently within each research paradigm, the popularity of focus groups is increasing (Carlsen & Glenton, 2011;George, 2013;Kress & Shoffner, 2007;Massey, 2010). The growth of focus groups within counseling and psychotherapy research has been predicated on recognition that focus groups offer an effective means to assess dispositions, attitude, ideas, and experiences (Pearson & Vossler, 2016).…”
mentioning
confidence: 99%
“…The growth of focus groups within counseling and psychotherapy research has been predicated on recognition that focus groups offer an effective means to assess dispositions, attitude, ideas, and experiences (Pearson & Vossler, 2016). Researchers have identified both benefits and challenges to using focus groups (Franz, 2011), but there are few guidelines for the planning and implementation of focus groups (George, 2013). Because scholars have recognized potential mechanisms of change within focus groups as an intervention (Debaere et al, 2016), it follows that effective focus group implementation includes group counseling skills (Kress & Shoffner, 2007).…”
mentioning
confidence: 99%